Study on pyrolysis characteristics of oil-rich coal under in-situ conditions and industrial-scale extraction simulation - Li, Xiao; Tang, Ying; Li, Youwu; Yang, Fan; Wu, Xiaodan; Sun, Jingyao; Cui, Jingyun; Zhang, Qing; Yuan, Siqi; Kang, ZhiQin (Frontiers in Earth Science, 2025)
IntroductionIn-situ pyrolysis technology for oil-rich coal represents a low-carbon resource development strategy characterized by ‘hydrogen extraction and carbon retention,’ holding significant importance for advancing the efficient exploitation of coal-based oil and gas resources. However, substantial differences exist between in-situ pyrolysis and conventional pyrolysis in terms of conversion efficiency and product composition, making the control of operating conditions a critical challenge in this field.MethodsThis study utilized large-sized block oil-rich coal samples from the Xie Gou mining area in Shanxi Province. Employing a self-developed, fully enclosed pyrolysis experimental system, the research simulated the high-temperature, high-pressure, slow-heating-rate, and long-duration reaction environment typical of in-situ pyrolysis. The distribution patterns of gaseous, liquid, and solid pyrolysis products from the oil-rich coal under varying temperatures were systematically investigated. Building upon the experimental results, industrial-scale simulations of oil-rich coal in-situ pyrolysis were conducted using COMSOL Multiphysics software.Results and DiscussionThe key findings are as follows: (1) The primary gaseous product of the pyrolysis reaction is CH4, with the total gas yield increasing significantly as temperature rises; (2) The temperature window of 450 °C–550 °C offers the potential for maximizing light oil recovery; (3) The stability of the carbon skeleton within the oil-rich coal enhances progressively as the pyrolysis reaction proceeds; (4) For industrial application, optimal oil production is achieved within approximately 500 days of heating, while optimal gas production occurs around 1900 days of heating. This study provides crucial theoretical support for the industrialization of oil-rich coal in-situ pyrolysis and demonstrates considerable application potential for the extraction of high-value oil and gas fuels.